An Historical Assessment of the Narrative Uses of the Words “Kabbalah,” “Cabala,” and “Qabala/h”: Discerning the Differences for Theological Libraries - Anthony J. Elia (Theological Librarianship, 2009)
Terminology surrounding the subject of “Kabbalah” has long been notoriously inconsistent and complex. What limited scholarly attention has been devoted to this quandary has in some cases served only to increase the confusion, resulting in significant problems for cataloging and for reference services.